Leadership in Family Businesses - Lee-Chua, Queena N (Archīum Ateneo, 2021)
This chapter presents leadership traits and strategies exemplified by first; second; and third generation leaders of successful Filipino family businesses. Recommendations for family businesses are given based on the cases presented in the chapter.